Monitoring the Chemical Profile in Agarwood Formation within One Year and Speculating on the Biosynthesis of 2-(2-Phenylethyl)Chromones - Ge Liao (Molecules, 2018)
Agarwood is highly valued for its uses as incense, perfume, and medicine. However, systematic analyses of dynamic changes of secondary metabolites during the process of agarwood formation have not yet been reported. In this study, agarwood was produced by transfusing the agarwood inducer into the trunk of Aquilaria sinensis, and changing patterns of chemical constituents, especially 2-(2-phenylethyl)chromones (PECs), in wood samples collected from the 1st to 12th month, were analyzed by GC-EI-MS and UPLC-ESI-MS/MS methods. Aromatic compounds, steroids, fatty acids/esters, sesquiterpenoids, and PECs were detected by GC-MS, in which PECs were the major constituents. Following this, UPLC-MS was used for further comprehensive analysis of PECs, from which we found that 2-(2-phenylethyl)chromones of flindersia type (FTPECs) were the most abundant, while PECs with epoxidated chromone moiety were detected with limited numbers and relatively low content. Speculation on the formation of major FTPECs was fully elucidated in our context. The key step of FTPECs biosynthesis is possibly catalyzed by type III polyketide synthases (PKSs) which condensate dihydro-cinnamoyl-CoA analogues and malonyl-CoA with 2-hydroxy-benzoyl-CoA to produce 2-(2-phenyethyl)chromone scaffold, or with 2,5-dihydroxybenzoyl-CoA to form FTPECS with 6-hydroxy group, which may serve as precursors for further reactions catalyzed by hydroxylase or O-methyltransferase (OMT) to produce FTPECs with diverse substitution patterns. It is the first report that systematically analyzed dynamic changes of secondary metabolites during the process of agarwood formation and fully discussed the biosynthetic pathway of PECs.